Balancing Transparency and Sustainability: Governance as a Moderator Between Carbon Emissions and Firm Value - Damayanti, Misvia; Chairunnisa, Nurlaila Maysaroh; Qintarah, Yuha Nadhirah (SAN Scientific, 2025)
This study aims to analyze the impact of carbon emission disclosure and annual report readability on firm value, while accounting for governance as a moderating variable. This study used companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) that published annual reports and sustainability reports, and disclosed information on carbon emissions during 2020-2022. The analysis results show that carbon emission disclosure has a significant positive effect on firm value. Conversely, annual report readability does not significantly affect firm value. Governance is shown to weaken the relationship between carbon emission disclosure and firm value. However, it does not moderate the relationship between annual report readability and firm value. The results of this study can inform the government in encouraging greater carbon emission disclosure in the basic materials industry, as disclosure is currently voluntary. Managerial Implications: The results of this study have important implications for company management in the basic materials sector, calling for greater attention to transparency and environmental communication strategies. Comprehensive carbon emission disclosure has been shown to increase firm value, so managers are advised to expand the scope and quality of carbon emission-related information in sustainability reports.